ULTRASONOGRAPHIC EVALUATION OF GASTRODUODENAL PATHOLOGY IN DOGS - Robert Cristian Purdoiu; Teodora Patrichi; Felix Daniel Lucaci; George Tudor; Radu Lăcătuș; Sorin Marian Mârza (Agricultura)
Gastrointestinal (GI) disorders are among the most common reasons for veterinary visits. Accurate diagnosis often requires imaging, with abdominal ultrasonography playing a key role alongside radiography. This study evaluated the utility of ultrasonography in diagnosing gastroduodenal pathology in dogs. Fifty-five canine patients with digestive signs were examined over 1 year. Ultrasonography was performed after 12-hour fasting using a high-frequency (7.5 MHz) transducer, assessing gastric and duodenal wall thickness, layering, motility, and adjacent structures. Key findings included gastric wall thickening (3.3–6.4 mm) and duodenal wall thickening (5.0–5.8 mm) in dogs with inflammatory gastroduodenal disease, compared to normal thickness of 3–5 mm. Wall layer architecture was preserved in most cases of gastritis, consistent with benign inflammation. Ultrasonography identified intestinal foreign bodies in many obstruction cases and evidenced gastric dilation in others. Approximately one-third of patients (13 of 55) required complementary barium contrast radiography for further evaluation, but in the majority, ultrasound findings alone guided diagnosis and treatment. Inflammatory conditions such as gastritis and gastroenteritis were the most prevalent diagnoses (62% of cases), with fewer cases of foreign body obstruction (25%), gastric dilatation (9%), and acute pancreatitis (4%). We conclude that abdominal ultrasound is a highly valuable first-line diagnostic tool for canine gastroduodenal disorders, revealing lesions and guiding management with minimal invasiveness. It provides detailed information on gastric/duodenal wall structure and motility, often obviating the need for contrast radiography. Ultrasonography should be employed routinely in dogs with chronic vomiting or suspected gastric pathology to improve diagnostic accuracy and clinical outcomes.